Exercising influence workbook : - Barnes, B. Kim (Pfeiffer, 2007)
Based on Kim Barnes bestselling book Exercising Influence, this Self-Study Guide shows you how to reflect on your “career” as an influencer and provides you with a structure for further growth and the development of your influence skills. Once you complete this guide you will have the basics needed to build relationships that will garner positive results in and outside your sphere of work